Customer experience with e-service quality for pt. Kereta api indonesia online ticket platform - Adhipradana Syafii, Ardiman; Aprianingsih, Atik (Journal of Business and Management, 2019)
With the advancement in technology and the easy access to the internet, many businesses shifted their attention to e-commerce. This advancement in technology made people have an easier access to their daily need with the help of the internet, with this even the transportation service industry also involved themselves by making an application to buy their ticket online, application such as traveloka and tiket.com offers a wide variety of ticket and proved that their application is used by a lot of people. With the rise of online ticketing PT KAI also launched their own application for their services which is the KAI Access application. This research is done to determine whether the KAI Access application have reached by the customer expectation by distributing a questionnaire to KAI Access user and to compare whether the KAI Access Application expectation by the consumer and the reality of KAI Access is the same and whether this expectation is affecting the Reuse Intention of their customer. The research was conducted by distributing a questionnaire involving KAI Access user. An amount of 219 respondent data was analyzed by using SPSS 20 and Microsoft Excel with the technique Importance Performance Analysis (IPA), multiple regression and assumption test. The result shows that the level of customer expectation is actually in a good level, similar to that of what customer perceived from KAI Access. With the perceived and expected customer perception towards KAI Access, the result shows that customer intention to reuse KAI Access is at a good level. Key words: PT KAI, KAI Access, Servqual